2002
DOI: 10.1590/s1413-86702002000500008
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax malaria presenting with severe thrombocytopenia

Abstract: Plasmodium falciparum and Plasmodium vivax malaria are endemic infections in India and are commonly associated with mild hematological abnormalities. Severe thrombocytopenia is common in isolated falciparum and mixed falciparum/vivax malaria, but is very rare in isolated P.vivax infection. We hereby report a case of severe thrombocytopenia (platelet count of 8x10 9 /L) in a case of vivax malaria. This is only the second case ever reported in the literature of such profound thrombocytopenia in a case of isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
51
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 9 publications
8
51
0
Order By: Relevance
“…In our study, the most common manifestation was thrombocytopaenia, which was reported in 90.2% of the cases and in about 37.0% children, severe thrombocytopaenia (<20,000/cumm) was present, with the lowest platelet count of 6000/cumm, which was probably the lowest count which was recorded among children in the literature [14][15][16][17][18]. There have been occasional reports of thrombocytopaenia with P.vivax malaria, either as an isolated or a more commonly associated complication [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 77%
“…In our study, the most common manifestation was thrombocytopaenia, which was reported in 90.2% of the cases and in about 37.0% children, severe thrombocytopaenia (<20,000/cumm) was present, with the lowest platelet count of 6000/cumm, which was probably the lowest count which was recorded among children in the literature [14][15][16][17][18]. There have been occasional reports of thrombocytopaenia with P.vivax malaria, either as an isolated or a more commonly associated complication [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 77%
“…These cases are often asymptomatic and are discovered under routine haematological investigations. 8 Hence, we planned the present study to analyse the clinical profile of febrile thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Although sever thrombocytopenia is commonly reported to be associated with Plasmodium falciparum infection and has been reported to occur in patients co infected with both Plasmodium falciparum and Plasmodium Vivax, its occurrence has been rarely reported in cases of Plasmodium vivax malaria. 16 The precise mechanism behind thrombocytopenia, however, remains unclear. Both the immunological as well as the nonimmunological destruction of platelets have been implicated.…”
Section: Discussionmentioning
confidence: 99%
“…Other postulates include peripheral destruction and the consumption of platelets. 16 Immune complexes which are generated by the malarial antigen lead to the sequestration of the injured platelets by the macrophages in the spleen. This is supported by the finding that malaria patients have elevated levels of platelet-bound IgG.…”
Section: Discussionmentioning
confidence: 99%